Electrical Resistivity and Conductivity - El Shahat, Adel (IntechOpen, 2017)
Motivated by the importance of electrical resistivity and conductivity, important experts in this field grasp most recent researches in this book. It addresses recent advances in electrical resistivity and conductivity modelling, measurement, estimation and sensing methods and implications. This book introduces innovative case studies for "Electrical Resistivity Sensing Methods and Implications", "Resistivity Model of Frozen Soil and High-Density Resistivity Method for Exploration of Discontinuous Permafrost", "Measurement of Electrical Resistivity for Unconventional Structures", "Estimation of Hydrological Parameters from Geoelectric Measurements" and "Assessment of Cryoprotectant Concentration by Electrical Conductivity Measurement and Its Applications in Cryopreservation". These recent advances are well prepared and presented in six chapters. These chapters are carefully selected to reflect current variable techniques, new concepts and methods related to the book's topic from different perspectives.